Establishment and Cross-Protection Efficacy of a Recombinant Avian Gammacoronavirus Infectious Bronchitis Virus Harboring a Chimeric S1 Subunit - Ting, Xiong; Xiang, Chengwei; Liu, Ding Xiang; Chen, Ruiai (Frontiers in Microbiology, 2022)
Infectious bronchitis virus (IBV) is a gammacoronavirus that causes a highly contagious disease in chickens and seriously endangers the poultry industry. A diversity of serotypes and genotypes of IBV have been identified worldwide and the currently available vaccines do not cross-protect. In the present study, an efficient reverse genetics technology based on Beaudette-p65 has been used to construct a recombinant IBV, rIBV-Beaudette-KC(S1), by replacing the nucleotides 21704-22411 with the corresponding sequence from an isolate of QX-like genotype KC strain. Continuous passage of this recombinant virus in chicken embryos resulted in the accumulation of two point mutations (G21556C and C22077T) in the replacement region. Further studies showed that the T248S (G21556C) substitution may be essential for the cell-adaptability of the recombinant virus. Immunization of chicks with the recombinant IBV elicited strong antibody responses and showed high cross-protection against challenges with virulent M41 and a QX-like genotype IBV. This study reveals the potential of developing rIBV-Beau-KC(S1) as a cell-based vaccine with broadly protective immunity against two different genotypes of IBV.